Order flow segmentation, liquidity and price discovery: The role of latency delays - Michael Brolley; David A. Cimon (Bank of Canada, 2018)
Latency delays - known as "speed bumps" - are an intentional slowing of order flow by exchanges. Supporters contend that delays protect market makers from high-frequency arbitrage, while opponents warn that delays promote "quote fading" by market makers. We construct a model of informed trading in a fragmented market, where one market operates a conventional order book and the other imposes a latency delay on market orders. We show that informed investors migrate to the conventional exchange, widening the quoted spread, while the quoted spread narrows at the delayed exchange. The overall market quality impact depends on the relative concentration of speculators who may become informed. If speculators are few relative to liquidity traders, total welfare falls; with relatively more speculators, total welfare rises.
Keywords: G14; G18; 330; Financial markets; Market structure and pricing; Financial system regulation and policies